A 14-Year-Old Boy with Torsion of the Epididymal Cyst. (21st December 2015) - Ameli, Mojtaba; Boroumand-Noughabi, Samaneh; Gholami-Mahtaj, Leila
Abstract : Epididymal cyst is a benign mass in the scrotum that is relatively common in adults but it is rare in children. In routine experience the treatment of such cysts is conservative. Torsion of these cysts is extremely rare and the diagnosis is made by exploration of the scrotum. Our patient was a 14-year-old boy who has been referred to hospital with scrotal pain followed by a minor trauma 3 days ago. Exploration of the scrotum to rule out testicular rupture was performed and a large black cyst connected to the head of the epididymis with 720-degree rotation was found. The cyst was resected and pathologic examination revealed an acquired epididymal cyst (spermatocele). The patient has normal physical exam after 3 months' follow-up.